Associations between relative abundances of Bifidobacterium species in the gut and DNA methylation of cortisol-related genes in a pediatric population - Harker, Samantha A.; Bonham, Kevin S.; McCann, Shelley Hoeft; Volpe, Alexandra R.; Zhu, Qiyun; D’Sa, Viren; Koinis-Mitchell, Daphne; Deoni, Sean C. L.; Klepac-Ceraj, Vanja; Lewis, Candace R. (Frontiers in Microbiology, 2025)
IntroductionHuman epigenetics, specifically DNA methylation, and the gut microbiome are dynamic systems influenced by environmental factors, such as diet and earlylife exposures, with profound implications for health and disease. Metabolites produced by the gut microbiome interact with the host, shaping physiological processes. While prior research has linked Bifidobacterium abundance to anxiety and cortisol function, the role of DNA methylation as a potential mechanism underlying these associations remains unexplored. This study examines the relationship between the relative abundance of Bifidobacterium species in the gut and DNA methylation of hypothalamic–pituitary–adrenal (HPA) axis genes in a pediatric cohort. We hypothesized that Bifidobacterium abundance would predict DNA methylation at key HPA genes associated with stress response, including NR3C1, FKBP5, and more.MethodsMultiple linear regression and regularized canonical correlation analysis (rCCA) were used.ResultsThere were significant associations between Bifidobacterium abundance and DNA methylation at HPA gene loci, while control analyses showed no association with global methylation levels. rCCA further pinpointed specific Bifidobacterium species, such as B. angulatum and B. adolescentis, as strong contributors to the first canonical component, correlating with CpG sites influencing HPA gene methylation.DiscussionThese findings suggest that microbiome-derived metabolites, such as folate, may modulate DNA methylation and stress physiology. This work provides new insights for exploring how the gut microbiome impacts mental health and stress resilience, offering potential pathways for microbiome-targeted interventions.